On the taxonomy of the genus Acronicta Ochsenheimer, 1816 (Lepidoptera, Noctuidae). I. Redescription of Acronicta grumi (Alphéraky, 1897), with notes on synonymy and its subgeneric placement - Volynkin, Anton V.; Matov, Alexej Yu.; Stüning, Dieter; Behounek, Gottfried (Zootaxa, 2015)
Acronicta Ochsenheimer, 1816 is a large genus of Noctuidae, with worldwide distribution mainly in the temperate zone. The genus includes more than 150 described species and is subdivided into nine subgenera (Sugi 1979; Fibiger et al. 2009; Kononenko 2003, 2010; Han & Kononenko 2010): Subacronicta Kozhanchikov, 1950, Jocheaera Hübner, [1820], Triaena Hübner, [1818], Hyboma Hübner, [1820], Viminia Chapman, 1890, Acronicta, Molybdonycta Sugi, 1979, Hylonycta Sugi, 1979 and Plataplecta Butler, 1878. A diagnosis of the genus was given by Fibiger et al. (2009) and Han & Kononenko (2010).